Values and Volume in Sustainable Organic Market Chains: A Multi-perspectival Analysis - Lamine, Claire; Noe, Egon Bjørnshave (The International Journal of Sociology of Agriculture and Food, 2018)
Values-based food chains (VBFCs) are investigated increasingly by various disciplinary perspectives, and with different outcomes in terms of understanding and recommendations issued to stakeholders. How can values be maintained throughout their growth process? VBFCs are complex study objects, which make different research perspectives such as coordination and organization, marketing and business logics, communication, mediation of values, resilience and sustainability relevant to address this key question. Rather than discussing which perspective is most favourable, the approach in the HealthyGrowth project has been a multi-perspectival approach. The aim of this article is to explore how this multi-perspectival analysis based on the perspectival findings of 19 European VBFC case studies help to assess key factors that in successful organic VBFCs allow integrity and trust to be maintained during growth from niche to volume. Three key processes were identified through which values can be upheld over time: 1. a continuous process of negotiation and sometimes redefinition of these core values; 2. a synchronization of time bindings and time horizons within the decision-making processes of the different agents involved; and 3. an extended understanding of professionalization that relates not only to the classical division of tasks but also to a diversity of skills. The multi-perspectival analysis provides an insight that is dependent on the perspectival findings, but not visible from any single perspective alone.